Earnings Quality, Leverage, Profitability and Corporate Cash Holdings: The Moderating Role of Institutional Investors in Indonesian Food and Beverage Firms - Dicky Rachmad Nugroho; Felisitas Defung (Universitas Muhammadiyah Sorong, 2026)
This study aims to examine the effect of earnings quality, leverage, and return on assets on corporate cash holdings, with institutional investors acting as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange during the 2020-2024 period. This research uses a quantitative approach with secondary data obtained from companies’ annual financial reports. The sample consists of 21 companies selected through purposive sampling, resulting in 105 firm-year observations. The data were analyzed using panel data regression with Moderated Regression Analysis (MRA). The results show that earnings quality and leverage have a negative and significant effect on corporate cash holdings, while return on assets has a positive but insignificant effect. Institutional investors moderate the relationship between earnings quality and leverage with corporate cash holdings by weakening their negative effects. However, institutional investors do not moderate the relationship between return on assets and corporate cash holdings. This study provides empirical evidence on the role of institutional investors in influencing corporate cash holding policies.